Mosquitoes - Perish, Patrick (2018)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces mosquitoes to young readers through leveled text and related photos"--
What are mosquitoes? -- In the wild -- Growing up.
Includes bibliographical references and index.
Age 5-8.
K to grade 3.
Keywords: Mosquitoes -- Juvenile literature